SEX-DIFFERENTIATED EDUCATION: AN ANALYSIS OF THE ACADEMIC AND SOCIAL IMPACT IN BASIC SECONDARY AND MIDDLE EDUCATION IN COLOMBIA - Gustavo Adolfo Picón Figueroa; Lizeth Karina Calderón Lindarte (DIALÉCTICA, 2025)
Do they promote learning or reinforce stereotypes? This question has led to the imaginary of increasing interest in academic and social training. It can be deduced that a heterogeneous education does not ensure equitable instruction, which is why differentiated education is needed to improve academic processes and coexistence. This is relevant when considering gender equity, as it invites reflection on the importance of differentiated education, both for interacting in learning according to the characteristics of each sex.